If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(3x + 2) + -8 = 0 Reorder the terms: 2(2 + 3x) + -8 = 0 (2 * 2 + 3x * 2) + -8 = 0 (4 + 6x) + -8 = 0 Reorder the terms: 4 + -8 + 6x = 0 Combine like terms: 4 + -8 = -4 -4 + 6x = 0 Solving -4 + 6x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 6x = 0 + 4 Combine like terms: -4 + 4 = 0 0 + 6x = 0 + 4 6x = 0 + 4 Combine like terms: 0 + 4 = 4 6x = 4 Divide each side by '6'. x = 0.6666666667 Simplifying x = 0.6666666667
| 6x-10=7x+2 | | .24-1= | | 96=1/2(360-x) | | 1-.24= | | 0.7+x+0.6=15 | | 2(2x-6)-(x+3)= | | 16(1-.24)= | | 5p-3q+2-4p+5+4q= | | -16-12x=16-14x | | (12*x*x*x*x)-5X^2=2 | | ab(a^2-2b)=0 | | 115=(105+x) | | 9-3÷1/3-1 | | 5(2u+4)-13u= | | 6x-x^2=7.2 | | 3,576923077*log(x/85) | | 3,576923077*log(x/85)-0.4=0 | | 8x+6y=65 | | -(u+6)-6u= | | 4x-4(-1x+19)=-164 | | 2420=2x | | 2x^(-1/2)-2=0 | | 4x-4(-x+19)=-164 | | 2420=2x+3 | | -6y=-7x+1 | | 9x^2+6x-48=-24 | | 2(4u+1)-5= | | f(x)=x^9 | | 5(4w+4)=-4 | | (6X+1)*(6X+1)=81 | | 38=1/2(180-x) | | X^2+3X+5X=-15 |